Analysis on quality of life and related factors in patients with depression - Rao Shuying; Xian Junding; Wan Chonghua; Lin Juda; Wen Jinfeng; Lin Meiling (Sichuan jingshen weisheng, 2022)
ObjectiveTo analyze the quality of life and related factors in patients with depression， and to provide evidence for formulating the corresponding measures to improve the patients' quality of life.MethodsA total of 117 inpatients who met the International Classification of Diseases， tenth edition（ICD-10） for depression were selected in Central People's Hospital of Zhanjiang， Affiliated Hospital of Guangdong Medical University and Guangdong 999 Brain Hospital from November 19， 2018 to September 7， 2019. The values of patients' clinical objective indicators consisted of routine blood test， routine urine examination， blood biochemical tests and blood gas analysis were collected by reviewing their medical records， and all subjects were assessed using Quality of Life Instruments for Chronic Diseases-Depression V2.0 ［QLICD-DE（V2.0）］. Simple correlation analysis was used to explore the correlation between the QLICD-DE （V2.0） scores and various clinical objective indicators， and multiple linear regression was adopted to further screen factors affecting quality of life of patients with depression.ResultsSimple correlation analysis suggested that QLICD-DE （V2.0） total score was positively correlated with total protein and platelet distribution width in patients with depression （r=0.198， 0.281， P<0.05 or 0.01）， and negatively correlated with hematocrit （r=-0.300， P<0.01）. Multiple linear regression analysis showed that albumin-to-globulin ratio and treatment compliance （B=-19.836， -3.711， P<0.05 or 0.01） were influential factors for physical function. Platelet distribution width （B=2.706， P<0.01） was an influential factor for psychological function. Bilirubin （B=-6.375， P<0.05） was an influential factor for social function. Platelet distribution width （B=2.101， P<0.05） was an influencing factor for specific module. The albumin-to-globulin ratio and platelet distribution width （B=-10.653， 2.114， P<0.05 or 0.01） were influencing factors for total score of QLICD-DE （V2.0）.ConclusionTreatment compliance and clinical objective indicators platelet distribution width， bilirubin and albumin-to-globulin ratio may be the influencing factors of quality of life in patients with depression.